Freedom Of Thought For Madrasah Ibtidaiyah Teachers In The Era Of Independent Curriculum - Qorina, Zulfia Al; Sutomo, Moh; Fatmawati, Erma; Uswah, Atiq Yufitriyah (ISTAWA, 2023)
The independent curriculum is a post-pandemic curriculum dream where the learning crisis is a multidimensional problem that cannot be solved by curriculum changes alone. The learning crisis can only be overcome by systemic changes. And that is what the Ministry of Education and Culture is now doing through a series of Merdeka Belajar policies in the independent curriculum. It has several principles, one of which was flexibility. This means that the school can implement this curriculum based on the environment. But this curriculum was very new when implemented by the teacher. The purpose of this study is to conceptually describe the Merdeka curriculum which is gradually implemented in MI Unggulan Nuris in grades 1 and 4 and will be implemented nationally in 2024. Descriptive qualitative research method of field research type is used as a research method. Data collection is done by interview, observation, and documentation methods. Data analysis used data reduction, data presentation, and conclusion drawing. Based on the research results, this curriculum can be applied in various fields. One teacher who prepared the independent curriculum attended training on curriculum for educational institutions. Based on interviews with teachers at Nuris Jember's madrasah ibtidaiyah, they responded enthusiastically to this curriculum although there are still shortcomings in its application. We hope that this implemented curriculum can achieve the goals in education in Indonesia.